Predictors of HIV-Risk Sexual Behavior: Examining Lifetime Sexual and Physical Abuse Histories in Relation to Substance Use and Psychiatric Problem Severity Among Ex-Offenders. (March 2014) - Majer, John M.; Rodriguez, Jaclyn; Bloomer, Craig; Jason, Leonard A.
BACKGROUND: Lifetime histories of sexual and physical abuse have been associated with increased HIV-risk sexual behavior, and some studies have identified other variables associated with these relationships. However, there is a dearth of literature that has critically examined abuse histories and HIV-risk sexual behavior in relation to these other variables.OBJECTIVES: Predictors of HIV-risk sexual behavior were analyzed among a sample of ex-offenders who were completing inpatient substance dependence treatment to identify factors related to increases in HIV-risk sexual behavior beyond that of abuse histories.DESIGN: Hierarchical linear regression was conducted to examine sociodemographic characteristics, recent substance use, and current psychiatric problem severity in addition to lifetime histories of sexual/physical abuse in a cross-sectional design.RESULTS: Gender, substance use, and psychiatric problem severity predicted increases in HIV-risk sexual behavior beyond what was predicted by abuse histories. Proportionately more women than men reported abuse histories. In addition, significantly more unprotected sexual than safer sexual practices were observed, but differences in these practices based on lifetime abuse histories and gender were not significant.CONCLUSIONS: Findings suggest recent substance use and current psychiatric problem severity are greater risk factors for HIV-risk sexual behavior than lifetime abuse histories among persons who have substance use disorders.